The Use Of Sense Of Humor In Motivating Covid-19 Sufferers For Quick Recovery During Independent Isolation - Tristiyani, Devi; Narti, Sri; Risdiyanto, Bayu (Universitas Dehasen Bengkulu, 2024)
Based on the background of the problem, the research aims to investigate the use of the concept of sense of humor in motivating Covid-19 sufferers who are undergoing self-isolation. This research uses qualitative research methods by using interviews, observation, and documentation as data collection techniques. The theory used in this research is the theory of aspects of sense of humor according to Thorsnon and Powel (1993). The results of the study showed (1) The ability of Covid-19 patients to produce humor while undergoing independent isolation at home. (2) The ability to cope with humor during self-isolation at home by addressing problems. (3) Appreciation of humor during independent isolation. They prefer to undergo independent isolation at home because they feel comfortable and safe. (4) Attitude towards humor. They really need positive humor from other people such as family and work relatives.